Comparative Analysis of Normalization Methods for Network Propagation - Biran, Hadas; Kupiec, Martin; Sharan, Roded (Frontiers in Genetics, 2019)
Network propagation is a central tool in biological research. While a number of variants and normalizations have been proposed for this method, each has its own shortcomings and no large scale assessment of those variants is available. Here we propose a novel normalization method for network propagation that is based on evaluating the propagation results against those obtained on randomized networks that preserve node degrees. In this way, our method overcomes potential biases of previous methods. We evaluate its performance on multiple large scale datasets and find that it compares favorably to previous approaches in diverse gene prioritization tasks. We further demonstrate its utility on a focused dataset of telomere length maintenance in yeast. The normalization method will be made available at http://anat.cs.tau.ac.il/WebPropagate upon acceptance of the paper.